A study of indirectness in Business Meetings - Lancy Fung (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2009)
The present study examines spoken interactions (with a focus on indirectness) performed by speakers in intercultural external meetings between a Hong Kong-based airline company and a bank on a co-branded credit card project. This study will firstly investigate how indirectness is applied when the communicative goals conflict, for example, when a speaker disagrees or intends to voice out a correction. Secondly, this study will examine the impact of power differences on the use of indirectness. This study suggests that indirectness may help speakers to increase the effectiveness of the message to be conveyed. In the business meetings, it is found that the functions of indirectness depend on the goal of the meeting and business relationships (for example, the power relationship) between the participants.